Pengaruh Teknik Relaksasi Genggam Jari Terhadap Nyeri Pasien Post Sectio Caesaria di Ruang Gardenia RSAB Pekanbaru - Murniasih, Elvi; Natalya, Rini; Eliawati, Umi (Initium Medica Journal, 2021)
One of the nursing care for post sectio caesarean patients was to prevent the occurrence of acute pain after surgery with an incision in the abdominal wall, both pharmacologically and non- pharmacologically. Pharmacologically it can be treated with analgesic drugs while non- pharmacologically it can be treated with relaxation techniques, one of which is finger grip relaxation techniques. Finger-held relaxation techniques are an easy way to manage emotions, develop emotional intelligence, help body, mind and spirit achieve relaxation. The purpose of this study was to determine the effect of finger grip relaxation techniques on pain in post sectio caesarean patients. This study used a quasy experimental design with a one group pre test post test design. The sample in this studied were 15 post sectio caesarean patients with a sampling technique, namely accidental sampling. The analysis performed was univariate and bivariate analysis. The statistical test used is Wilcoxon. Post sectio caesarean maternal pain scale before finger grip relaxation action is 5.07 and after finger grip relaxation action is 3.13. The results of the analysis showed that the p value = 0.002 (α <0.05) means that it can be concluded that there is an effect of finger grip relaxation techniques on pain in post sectio caesarea patients in the gardenia room of Awal Bros Hospital (RSAB) Pekanbaru. With this research, Pekanbaru Hospital can make policies and Operational Procedural Standards (SPO) regarding finger grip relaxation techniques.